THE ROLE OF CORPORATE SOCIAL RESPONSIBILITY IN MODERATIONG PROFITABILITY AND TAX AVOIDANCE IN THE PROPERTY, REAL ESTATE AND BUILDING CONSTRUCTION SECTORS IN 2014-2017 - Radhi Abdul Halim Rachmat; Hafied Noor Bagja; Yoga Tantular Rachman (Jurnal Ekonomi, 2023)
This study aims to find out whether profitability affects tax avoidance in the property, real estate and building construction sectors in 2014-2017 with corporate social responsibility (CSR) as a variable Moderate. The population in this study was 144 companies, real estate and construction in the 2014-2017 time frame. Using the purposive sampling method, 68 samples were obtained. The results showed that the data had met the requirements of classical assumptions, followed by hypothesis testing using multiple linear regression analysis and Moderated Regression Analysis (MRA). The test results show that profitability has a significant positive effect on tax avoidance, and the CSR variable as a moderating variable strengthens the positive effect of profitability on tax evasion